ANALYSIS OF DIFFERENCES IN SELF-REGULATED LEARNING AMONG ELEMENTARY SCHOOL STUDENTS - Mumun Muntasiroh; Riandi Marisa; Indra Jaya (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to examine gender differences in self-regulated learning (SRL) among elementary school students and to identify variations across SRL components. A quantitative approach with a comparative survey design was employed. The sample consisted of 60 fifth-grade students selected through total sampling. Data were collected using an SRL questionnaire and analyzed using descriptive statistics and an independent sample t-test. The results revealed a significant difference in SRL between male and female students (p < 0.05), with female students obtaining higher SRL scores. Differences were consistently found across all SRL components, particularly in planning and reflection. These findings indicate that variations in self-regulated learning are not only reflected in overall scores but also in its underlying dimensions.The study provides a more detailed profile of elementary students’ SRL based on gender across multiple components. The findings highlight the importance of early SRL development through adaptive and differentiated instruction to support students’ learning independence.